PID/WAG-mediated phosphorylation of the Arabidopsis PIN3 auxin transporter mediates polarity switches during gravitropism - Grones, Peter; Abas, Melinda; Hajný, Jakub; Jones, Angharad; Waidmann, Sascha; Kleine-Vehn, Jürgen; Friml, Jiří (Scientific reports, 2018)
Intercellular distribution of the plant hormone auxin largely depends on the polar subcellular distribution of the plasma membrane PIN-FORMED (PIN) auxin transporters. PIN polarity switches in response to different developmental and environmental signals have been shown to redirect auxin fluxes mediating certain developmental responses. PIN phosphorylation at different sites and by different kinases is crucial for PIN function. Here we investigate the role of PIN phosphorylation during gravitropic response. Loss- and gain-of-function mutants in PINOID and related kinases but not in D6PK kinase as well as mutations mimicking constitutive dephosphorylated or phosphorylated status of two clusters of predicted phosphorylation sites partially disrupted PIN3 phosphorylation and caused defects in gravitropic bending in roots and hypocotyls. In particular, they impacted PIN3 polarity rearrangements in response to gravity and during feed-back regulation by auxin itself. Thus PIN phosphorylation, besides regulating transport activity and apical-basal targeting, is also important for the rapid polarity switches in response to environmental and endogenous signals.
Keywords: Arabidopsis Proteins; sekvence aminokyselin; percepce tíhy; Indoleacetic Acids; Amino Acid Sequence; proteiny huseníčku; polarita buněk; fosforylace; Plant Roots; kyseliny indoloctové; Cell Polarity; Arabidopsis; Gravity Sensing; regulátory růstu rostlin; kořeny rostlin; Gravitropism; Phosphorylation; gravitropismus; Plant Growth Regulators